A prospective, randomized, double blind controlled trial of the use of preoperative antibiotics in routine abdominal surgery: A comparative analysis between Ofloxacin + Metronidazole, Cefotaxime + Sulbactum and Cefepime +Tazobactum (Single does vs. Three - Narendra N Ganguly; Rituparna Phukan Ray; M Lahkar; Aisha Siddiqui (International Journal of Medical Research and Review, 2016)
Introduction: Anti microbial prophylaxis before any elective surgery is a preferred deterrent to post operative surgical site infection now. We have used different antibiotics, two being from the cephalosporin class, one from the fluoroxoqiuinolones and anti beta lactamases in combination along with metronidazole. The aim was to find out the best and most economical pre operative prophylaxis in our surgical practice. Three antibiotics regimens were studied. Patients were divided into two groups against each agent of Ofloxacin +Metronidazole, Cefotaxime + Sulbactum and Cefepime +Tazobactum. They were again subdivided into two groups one receiving single dose and another three doses of the antibiotics regimens.Methods: A total of 138 patients (above 16 years) were taken for the study. It was a randomized and blind study. Patients were prospectively analysed. First, the patients were divided into two groups. First group received a single dose of antibiotic at incision and those who received two more doses at eight hours interval after the dose at incision.Discussion: The single dose pre operative prophylaxis scored over three doses regime in all the cases for lap surgery irrespective of OT condition. Three doses regime worked better in combined OT condition for the open elective procedures. The study also revealed the most economic choice for routine elective abdominal surgery.Conclusion: Multiday and antibiotics use for a prolonged period is not advisable these days after a routine elective abdominal surgery. Single dose injection of antibiotics at a proper time is good enough for preventing postoperative surgical site infection after a routine Laparoscopic surgery. Three doses regime is better in open surgical cases performed in OTs where emergency procedures are undertaken. It is advisable to use the most cost effective regime to reduce the healthcare cost in the country.